Determinants of quality incentives in a mutual fund duopoly - M. LEMEUNIER, SÉBASTIEN (Bankers, Markets & Investors, 2021)
While a trend of literature stresses that worse before-fee performing mutual funds set relatively high fees, we raise an issue about the determinants of quality incentives in a mutual fund market. With an economic model where mutual funds are vertically differentiated and in which all investors are sophisticated, we demonstrate that mutual funds with different quality levels adopt the same strategic fee-setting in any circumstances. This fee-setting strategy and the asymmetric information allow the opportunism of a low-quality mutual fund and induces the high-quality one to deliver a high level of quality.